Implementation of Guarantees for the Rights to Education Correctional Students While in Prison - Putri Augustine; Ahmad Irzal; Maya Shafira; Firganefi Firganefi; Dona Raisa Monica (Faculty of Law, Musamus University, 2023)
A child in conflict with the law, who is then sentenced and placed in the Special Child Development Institution (LPKA), has the right to receive supervision, assistance, training, guidance and the right to education in accordance with the mandate and provisions of the relevant law. This research discusses the application of Guaranteed Educational Rights for Correctional Students (Andikpas) in Class II LPKA Bandar Lampung with the legal issue behind this research is that there are several LPKAs in Indonesia that have not paid attention to the right to education for Andikpas. Based on these legal issues, the problem in this research is related to the application of education rights guarantees in the sentencing of Andikpas at LPKA Class II Bandar Lampung and what are the inhibiting factors for implementing education rights guarantees in the sentencing of Andikpas in LPKA Class II Bandar Lampung. This research uses normative legal research methods which are supported by empirical research. Sources of primary data collection were carried out through field studies by conducting interviews with LPKA structural officials, LPKA employees, Andikpas representatives, and lecturers in the Criminal Law section of the Faculty of Law, University of Lampung. Secondary data collection is done by literature study. The data that has been obtained by the author is then analyzed qualitatively. The results of the research carried out show that the implementation of the Education Rights Guarantee at LPKA Class II Bandar Lampung for Andikpas has been implemented, but not yet fully implemented properly. The forms of education available include formal and non-formal education. For formal education, there are Package A (SD), SMP, and SMA equivalency education programs that work independently with the Dwi Mulya Foundation. Non-formal education can be said to be a skills and training activity in which Andikpas are fostered and trained in their skills through various activities prepared by LPKA on a regular basis. In carrying out the implementation of education, of course, they are faced with various kinds of obstacles, including legal factors, namely there are no specific technicalities in legislation that show how to apply education to Andikpas. Law Enforcement Factors, namely there are still deficiencies in quality and quantity in coaching officers. Factors of Facilities and Infrastructure, which are still classified as limited and not sufficient enough. Community factors, regarding the negative stigma against Andikpas who have returned to social life. And Cultural Factors, cultivate laziness from within Andikpas in carrying out educational obligations. In this way, LPKA strives fully, whatever becomes an obstacle in implementing the implementation of education and the Head of LPKA Class II Bandar Lampung hopes that the education and coaching that has been held can develop the potential of children so that when they return to social life they are still educated and can play an active and responsible role.